2016
DOI: 10.1007/s10709-016-9883-4
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted patterns of genetic differentiation across eight bird species in the Lesser Antilles

Abstract: Archipelagoes are considered as "natural laboratories" for studying processes that shape the distribution of diversity. The Lesser Antilles provide a favorable geographical context for divergence to occur. However, although morphological subspecies have been described across this archipelago in numerous avian species, the potential for the Lesser Antilles in driving intra-specific genetic divergence in highly mobile organisms such as birds remains understudied. Here, we assessed level of intra-specific genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Bullfinches in particular were selected for this study because they were common birds in all the studied forest fragments, from pristine to degraded ones. Although no data are available regarding its dispersal ability, previous studies revealed detectable genetic structure in this species both between islands (Khimoun et al 2016a) and within the island of Guadeloupe (Khimoun et al 2017), suggesting that the species is not very mobile.…”
Section: Study Species and Field Samplingmentioning
confidence: 83%
See 2 more Smart Citations
“…Bullfinches in particular were selected for this study because they were common birds in all the studied forest fragments, from pristine to degraded ones. Although no data are available regarding its dispersal ability, previous studies revealed detectable genetic structure in this species both between islands (Khimoun et al 2016a) and within the island of Guadeloupe (Khimoun et al 2017), suggesting that the species is not very mobile.…”
Section: Study Species and Field Samplingmentioning
confidence: 83%
“…Whereas the subspecies L. n. dominicana and L. n. noctis are described in Guadeloupe and Martinique respectively, genetic analyses do not seem to support this subspecific differentiation between islands (Khimoun et al 2016a). Although no data are available regarding its dispersal ability, previous studies revealed detectable genetic structure in this species both between islands (Khimoun et al 2016a) and within the island of Guadeloupe (Khimoun et al 2017), suggesting that the species is not very mobile. Within the species range, bullfinches inhabit all kinds of forested habitats, from continuous evergreen forest to regrown forest fragments among cultivation fields (Rising and Jaramillo 2016).…”
Section: Study Species and Field Samplingmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Muscarella, Murray, Ortt, Russell, and Fleming (), Carstens et al (), and Larsen et al () found varying population structuring in different species of phyllostomid bats in the Caribbean, ranging from some species having monophyletic populations confined to individual islands, and other species lacking any genetic structuring among islands. Similar patterns have also been observed in other groups of volant animals, such as butterflies (Davies & Bermiham., ) and birds (Khimoun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although birds have long been regarded as less sensitive to habitat fragmentation than other taxa because of their assumed high dispersal abilities, recent works have shown that gene flow can be restricted over very short geographic distances in avian species (Arnoux et al., ; Bertrand et al., ; Khimoun, Arnoux, et al., ; Khimoun, Eraud, et al., ). In addition, a previous study based on the comparison of a continuous forest and a fragmented forest within a small island revealed that forest fragmentation affects population genetic structure in several bird species at a small spatial scale and that forest specialist species are more impacted than co‐occurring generalist species (Khimoun, Eraud, et al., ).…”
Section: Introductionmentioning
confidence: 99%